2007
DOI: 10.1159/000102595
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Nitroprusside Regulates mRNA Expressions of LTC4 Synthesis Enzymes in Hepatic Ischemia/Reperfusion Injury Rats via NF-κB Signaling Pathway

Abstract: Leukotriene (LT) C4 (LTC4) synthesis enzymes including LTC4 synthase (LTC4S), microsomal glutathione S-transferase (MGST) 2 and MGST3 can all conjugate LTA4 and reduced glutathione (GSH) to form LTC4, which is related to hepatic ischemia/reperfusion (I/R) injury. The relationship between nitric oxide (NO) and cysteinyl LTs has been shown in previous studies. However, the mechanisms of NO action on gene expression of LTC4 synthesis enzymes are still largely unclear during hepatic I/R. Adult male Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
1
10
0
2
Order By: Relevance
“…In fact, the relationship between nitric oxide (NO) and cysteinyl LTs has been demonstrated in previous studies. Yang et al [40] have shown that sodium nitroprusside, a nitric oxide donor, down-regulates the mRNA expression of LTC 4 synthesis enzymes in hepatic ischemia/ reperfusion injury in rats via the NF-kappaB signaling pathway. Our results are consistent with those of Ko and Cho [41], who observed a reduction in the level of LTC 4 after administration of L-NAME (an inhibitor of nitric oxide synthesis).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the relationship between nitric oxide (NO) and cysteinyl LTs has been demonstrated in previous studies. Yang et al [40] have shown that sodium nitroprusside, a nitric oxide donor, down-regulates the mRNA expression of LTC 4 synthesis enzymes in hepatic ischemia/ reperfusion injury in rats via the NF-kappaB signaling pathway. Our results are consistent with those of Ko and Cho [41], who observed a reduction in the level of LTC 4 after administration of L-NAME (an inhibitor of nitric oxide synthesis).…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of organic nitrates is the induction of drug tolerance with prolonged continuous use. NO release from nitroglycerin is likely via the enzyme, mitochondrial aldehyde dehydrogenase [53] . The mechanism of NO release from sodium nitroprusside, on the other hand, is more complex, as demonstrated by Yang et al [53] in a murine model of hepatic IRI.…”
Section: No Donor Drugsmentioning
confidence: 99%
“…NO release from nitroglycerin is likely via the enzyme, mitochondrial aldehyde dehydrogenase [53] . The mechanism of NO release from sodium nitroprusside, on the other hand, is more complex, as demonstrated by Yang et al [53] in a murine model of hepatic IRI. Sodium nitroprusside is thought to down-regulate the mRNA expression of several enzymes related to hepatic injury [54] .…”
Section: No Donor Drugsmentioning
confidence: 99%
“…The main limitation of organic nitrates is the induction of drug tolerance with prolonged continuous use. NO release from nitroglycerin is likely via the enzyme mitochondrial aldehyde dehydrogenase (Yang, Chen, Kong, Xu, & Lou, 2007). On the other hand, the mechanism of NO release from sodium nitroprusside is more complex as demonstrated by Yang et al in a murine model of hepatic IRI.…”
Section: No Donor Drugsmentioning
confidence: 99%